Uma genealogia da participação política em Portugal e no Brasil - Liberatti, Angela Inês (2019)
The research is a genealogy of politically participation on Portuguese and Brazilian urban, as of the assumption that common interest for subjects of urban spaces were constituted in a secular history in Portugal and it was not possible to transfer this experience to Brazil. The Portuguese urbanization was a result of a millenary process of many influences, as well as the possibilities of politically participation and its institutions that, historic constituted, enabled the emergence of a politic culture that superimposed even the absolute State. A genealogy of politically participation of urbans institutions in Portugal, indicate the impossibility of reproduction, in Brazilian colony, of the Portuguese model. In its history, Brazil reversed the Portuguese logic, whre the institution that should be politically participation had become the reaffirmation of elite impositions. The Portuguese rural tradition and the construction of a culture related to land was brought to Brazil since XVI century. However, there is a lot to take into consideration regard the meaning of use of land, of urban e how forms of politically participation were built in these two spaces distanced from the use and embate that produces their histories and truly regimes. In a continuous history Portuguese traditions could be found in Brazil. The option for genealogy that allow us to verify ruptures and discontinuity. In Portugal, the rural and urban councils formation process enabled since ever, even with miss use, the possibility of politically participation, the conventos publicus vicinorum. Brought to Brazil, this possibility was excluded because what was called popular representation, e its institutions, such as City Council, are different practices that currently are problematic for politically participation. In Portugal, even during times of royal power concentration there was always attachment to councils autonomy, to politically participation possibilities and to regional speeches, observed now a days on local institutions. Different from Brazil where the local power was held by land proprietary of elitist institutions from which social order was more imposed than consensual, and even following Portuguese judicial order, became something else, much different than Portuguese institution. At a society constituted by few rich men, saw by Portuguese as honored, that has stablished since the beginning an elite favored by recompenses, such as tittles by the Portuguese king, or his Brazilian participation, the issues were others, not the fight for participation. In these diverse context that we may understand the political practice that derivate the City Councils and the historic of current popular democratic representation or its reverse side, not only in Portugal but also in Brazil